Kaji Eksperimen Sistem Pendingin Adsorpsi Double Bed Adsorber Pada Temperatur Desorpsi 85° C Dengan Silika Gel-Air Sebagai Pasangan Adsorben-Adsorbat - Moh. Arief Indra Permana; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
he adsorption cooling system is one of the technologies for air conditioning and refrigeration systems that are energy efficient and environmentally friendly. The double bed adsorption cooling system with silica gel as adsorbent and water as an adsorbate, and the performance of the system were examined experimentally. The adsorption cooling system consists of two u-tube adsorber with finned tube structure, evaporator, condenser, one heater and one cooling, and is equipped with additional measuring instruments and system components. Based on the test data and calculations obtained, the COP value of the adsorption cooling system is 0.295 at the time of operation 1200 s with a desorption temperature of 85 ° C. The SCP value obtained is 0.04. The average temperature of chilled water that comes out of the evaporator for 1 minute is the adsorption process, for adsorption of adsorber 2 the average temperature of chilled water coming out of the evaporator is 28.3 ˚C with the chilled water temperature entering the evaporator 30.06 ˚C, and for adsorption adsorber 1 the average temperature of the chilled water coming out of the evaporator is 27.82 ˚C with the chilled water temperature entering the evaporator 29.31 ˚C. Keywords: Adsorption, Desorption, Cooling System, Adsorbent-Silica Gel, Two Bed